1999
DOI: 10.1080/02791072.1999.10471723
|View full text |Cite
|
Sign up to set email alerts
|

Level of Burden Among Women Diagnosed with Severe Mental Illness and Substance Abuse

Abstract: Women diagnosed with severe mental illness and substance abuse may face a variety of associated difficulties that require intervention, including other health-related problems, housing instability or homelessness, and a history of or current physical or sexual abuse. This article expands upon the concept of "level of burden" by specifically examining issues for women with multiple vulnerabilities in a sample of 577 women participating in a residential substance abuse treatment program. Two types of outcomes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 25 publications
1
25
1
2
Order By: Relevance
“…However, DD clients may face greater obstacles in seeking to achieve abstinence [67] and therefore may often not be accepted at such services. This shortfall of treatment availability stands in contrast to current recommendations to provide long-term support as in DD clients, positive outcomes are less likely to be achieved by brief interventions [68][69]. Hence such findings may prompt questions about the extent to which service eligibility criteria are tailored towards DD clients.…”
Section: Discussioncontrasting
confidence: 45%
“…However, DD clients may face greater obstacles in seeking to achieve abstinence [67] and therefore may often not be accepted at such services. This shortfall of treatment availability stands in contrast to current recommendations to provide long-term support as in DD clients, positive outcomes are less likely to be achieved by brief interventions [68][69]. Hence such findings may prompt questions about the extent to which service eligibility criteria are tailored towards DD clients.…”
Section: Discussioncontrasting
confidence: 45%
“…While mixed-gender samples allow for examination of gender-specific predictors of retention, a number of studies have examined predictors of retention among women-only samples (Brown et al, 1995;Davis, 1994;Hughes et al, 1995;Huselid et al, 1999;Haller and Miles, 2004;Kelly et al, 2001;Knight et al, 1999;Loneck et al, 1997;Stahler et al, 2005;Szuster et al, 1996). Research using women-only samples has found associations between certain patient characteristics (e.g., psychological function, personal stability and social support, levels of anger, treatment beliefs, and referral source) and rates of retention and completion.…”
Section: Individual Characteristics Associated With Treatment Retentimentioning
confidence: 99%
“…Kelly et al (2001) reported that having fewer children, higher levels of personal stability, less involvement with child protective services, and fewer family problems predicted treatment completion among 34 women in a women-centered program. Brown et al (1995) found that among 203 women in residential treatment, those with a high level of burden (measured by the number and severity of psychological, cognitive, health, and substance abuse problems) had lower retention rates than those with lower levels of burden. In one sample of 80 women in outpatient drug treatment, anger was the strongest predictor of treatment dropout (Davis, 1994).…”
Section: Individual Characteristics Associated With Treatment Retentimentioning
confidence: 99%
“…Ces pa tients quit tent le trai te ment pré ma tu ré ment et ont de la dif fi culté à s'en ga ger dans un pro ces sus de chan ge ment ainsi qu'à éta blir une al liance thé ra peu ti que (Brown et al, 1999 ;Gill et al, 1992 ;Lu borsky et al, 1985 ;Mer cer et al, 1997 ;Ver heul et al, 1998Ver heul et al, et 2000. En somme, le trai te ment leur est moins bé né fi que.…”
Section: éDitorialunclassified